A community service learning experience with student teachers of English: enacting social justice in language education in a community centre. Issue 2 (4th March 2023) - Porto, Melina
ABSTRACT : This article reports a service learning experience carried out by volunteer university student teachers of English during 2017–2018 in a non-governmental organisation in Argentina. In collaboration with their university teachers, they taught workshops using intercultural literature in English for underserved children aged 8-12. Drawing on intercultural citizenship theory and intercultural service learning, which both combine language learning with citizenship goals and social justice and human rights foundations, the aim of the service learning experience was to challenge the conditions of possibility for the children involved. Designed as a case study in combination with action research, varied data types were collected (reflection logs, workshop plans, teacher field notes, artefacts created by the children, photographs and video-recordings of workshops). Qualitative data analysis involved three phases (holistic, inductive and deductive). Findings are presented in a vignette with glimpses of an ethnographic description of the context and a narrative account of the first workshop intended to portray the 'conditions of possibility' in the setting. The study shows that language learning was transformatory as the children took small actions in their social milieu using varied semiotic resources to convey their messages. Implications for language education with a social justice basis are discussed.